The Impact Of The Socio-Cultural Environment During The Abbasid Dynasty On The Development Of Theological Thought - Abdullayev Abdurasul Abdulpattoyevich (Periodica Journal, 2025)
This article provides information about the development of science and culture during the Abbasid dynasty, the "Mihna" policy, that is, debates about whether the Holy Quran was created or not, the translation of several books on astronomy, mathematics, philosophy, medicine, history, and literature from various languages into Arabic during the reign of Caliph al-Mansur, and the emergence of the palace library that became the basis for the creation of "Bayt alhikma." The article also presents the views of scholars and researchers on the developed socio-cultural environment and the development of theological thought during the Abbasid dynasty.
Keywords: The Abbasid dynasty; Mihna; politics; Harun al-Rashid